2020
DOI: 10.1002/cbic.202000465
|View full text |Cite
|
Sign up to set email alerts
|

Photocaged Hoechst Enables Subnuclear Visualization and Cell Selective Staining of DNA in vivo

Abstract: Selective targeting of DNA by means of fluorescent labeling has become a mainstay in the life sciences. While genetic engineering serves as a powerful technique and allows the visualization of nucleic acid by using DNA‐targeting fluorescent fusion proteins in a cell‐type‐ and subcellular‐specific manner, it relies on the introduction of foreign genes. On the other hand, DNA‐binding small fluorescent molecules can be used without genetic engineering, but they are not spatially restricted. Herein, we report a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…One of their conjugates, 5′-580CP-Hoechst was used to obtain high-resolution images of DNA and tubulin structures in intact animal erythrocytes, demonstrating practical applications for live cell imaging. Lämmle et al reported a photocaged Hoechst dye (pcHoechst; 12 ) which allows the spatiotemporal control of subnuclear DNA labeling [ 25 ]. Their probe was nontoxic for cells and zebrafish and specifically stained subnuclear DNA upon UV irradiation, suggesting that the probe can be used for not only chromosomal DNA, but also extranuclear DNA during viral entry events or tumor-specific mutations.…”
Section: Design Strategies and Recent Examplesmentioning
confidence: 99%
“…One of their conjugates, 5′-580CP-Hoechst was used to obtain high-resolution images of DNA and tubulin structures in intact animal erythrocytes, demonstrating practical applications for live cell imaging. Lämmle et al reported a photocaged Hoechst dye (pcHoechst; 12 ) which allows the spatiotemporal control of subnuclear DNA labeling [ 25 ]. Their probe was nontoxic for cells and zebrafish and specifically stained subnuclear DNA upon UV irradiation, suggesting that the probe can be used for not only chromosomal DNA, but also extranuclear DNA during viral entry events or tumor-specific mutations.…”
Section: Design Strategies and Recent Examplesmentioning
confidence: 99%
“…For instance, 4′‐580CP‐Hoechst [47] and SiR‐Hoechst (also known as SiR‐DNA) [48] are red and far‐red DNA stains, respectively, that are STED compatible and a “healthier” alternative (Figure 3). We recently reported a photocaged DNA stain termed pcHoechst, which was used to label sub‐compartmental regions of nuclear DNA in live cells and allowed in vivo DNA tracking in the zebrafish ( Danio rerio ) while ensuring animal health [49] . These modern DNA targeting stains offer great potential in parasite research but have hitherto not been used to examine P. falciparum .…”
Section: Chemical Biology Tools In Plasmodium Falciparum Researchmentioning
confidence: 99%
“…However, the majority of studies still examine the apicoplast via immunofluorescence analyses or transgenic P. falciparum strains. The above‐mentioned pcHoechst is a probe with great potential to label the DNA and indirectly investigate the behaviour of the apicoplast [49] . Similarly, micronemes, rhoptries and dense granules are secretory organelles involved in RBC infection and reorganization [78,79] .…”
Section: Chemical Biology Tools In Plasmodium Falciparum Researchmentioning
confidence: 99%
See 2 more Smart Citations